Failure analysis of sintered B4C due to thermal shock - Loh, Debbie Ling Man (2014)
Spark Plasma Sintering (SPS) Technique in producing Boron Carbide is one of the top choices for defense applications. SPS can produce dense material up to 99 % of its theoretical value in a very short time (few minutes).(U, Jurgen et al.) Boron carbide is widely known for its combination of excellent properties of low density, high hardness, good absorption of neutrons and very stable to ionize radiation and many chemicals.(Garrett 1998) However, due to Boron Carbide’s brittleness and particularly susceptible to thermal shock, it has been a real problem, which prevents large-scale production. Therefore, this project will looked into the effects of cooling rate and press force on the mechanical properties, densification and also the ability to stay intact during sintering. SEM images of the surface morphology were also studied to analyze the inhomogeneous sintering due to fast cooling rate. Experimental results shows that although fast cooling rate due to less time taken will gives small gain size thus theoretically leading to high fracture strength. However, results shows that high cooling rate samples have a higher probability of failure. This leads us to another theory of thermal shock where difference in temperature gradient will lead to inconsistent expansion and compression, thus causing material failure. Furthermore, results also show that increase press force applied gives a lower densification and also more likely to stay intact during the sintering process This defies the actual theory of higher press force gives higher densification and we concluded that the effect of cooling rate in densification may be higher than the maximum press force applied. Lastly, the slower rate of press force applied gives higher densification due to electro-migration of ions.